‘When spider webs unite they can tie up a lion’: anti-racism, decolonial options and theories from the South - Murrey, A (Routledge, 2018)
This chapter focuses on two discrete but interrelated intellectual projects: Southern theory and decolonial options. With a focus on race-aware and anti-racist critiques of Southern theories, Murrey argues that assertions of the need to focus more centrally on Southern theory are not equivalent with assertions of the need to end, unequivocally, the coloniality of knowledge. Some of the critical and celebrated scholarship critiquing the (ongoing) hegemony of Eurocentric theory and knowing – broadly, theories from the South – has failed to systematically engage with the racialisation of actors within the university and racial inequality in knowledge making. In such paradigms, Southern theories are importantly recognised as valuable for shifting the gaze while, at the same time, there remains a certain blindness to the colonial racial hierarchies that create and sustain the invisibilisation(s) and destructions of them. Situated in the context of coloniality, such projects risk reiterating the global knowledge hierarchy. Murrey sketches an alternative: a feminist decolonial orientation founded on an open assessment of racial and geographical inequalities within the university along with a critical feminist attention to the politics of the mundane in the academy (authorship, citation, language, promotion and impromptu encounters in classrooms and corridors).